Multidose pharmacokinetic study of azithromycin in pneumonic foals - Rivulgo, Virginia Margarita (2009)
Azithromycin (AZM) is an azalide antibiotic commonly used in Human and Veterinary Medicine, for the treatment of respiratory diseases. Rhodococcus equi is an intracellular facultative Gram positive pathogen that provokes pneumonia in foals. Pharmacokinetics (PK) of AZM in diseased foals has not been still described. The main goal of this study was to evaluate the plasma PK of AZM in a multiple dose regimen in experimentally challenged R. equi -foals-infection model of pneumonia. Five foals of 42 days old were inoculated by intratracheal endoscopy, with 25 mL of a 103 R. equi 103+ strain solution. When the disease developed, foals were treated orally with 10 mg/kg of AZM q 24 h for 6 days. Blood samples were obtained from jugular vein. Samples were frozen up to analysis by bioassay method using Kocuria Rhizophila. Cmax was obtained at 2 hours after the first and latest administration. Comparison between values of AUC 0-24 (14.0 ± 2.95 μg.h/ml) and AUC 120-144 (18.0 ± 5.00 μg.h/ml) showed no statistical difference. These values pointed out that the steady state was not attained, being 6 days of treatment insufficient to obtain clinical and bacteriological cure.